Optimal commuting and migration decisions under cost uncertainty - Christian Schmidt (European Regional Science Association (ERSA), 2010)
In recent decades, many countries have experienced suburbanization processes in metropolitan areas that have lead to an increase in urban sprawl by creating a growing polarity between newly formed satellite communities and the central urban area. More than before, work and residence location diverged. In this context, commuting and migration are two fundamental ways of connecting an individual's place of work with his residence. These distinctive mobility modes represent temporary and permanent mobility, respectively. Deciding for any of the two incurs peculiar costs. Commuting requires recurring costs that the individual has to bear without permanently changing his residence. In contrast, migration relocates the place of residence and can therefore prevent periodical mobility costs. Due to this fact, migration can serve as an alternative to commuting in respect to connecting the place of residence with the work place. This paper represents work in progress on the individual decision between commuting and migrating to the place of work in face of uncertain commuting costs. Solutions for two initial states are derived on the basis of the real options theory. The threshold commuting cost levels at which it is optimal for the individual to relocate to the suburb when initially living in the metropolitan center and to relocate to the city center when initially living in the suburb are presented and compared to the classical net present value solution without uncertainty about commuting costs. The effect of uncertainty about the evolution of commuting costs on the optimal decision denotes a remarkable result of this model: higher uncertainty lowers the commuting cost threshold for outmigration to the suburb, while increasing it for inmigration to the city center. On the one hand, individuals initially not commuting but living in the city center deter a possible outmigration even under increasingly unfavorable rental cost conditions. On the other hand, individuals initially living in the suburb are willing to bear significantly higher commuting costs before eventually relocating to the metropolitan center.
Keywords: 330; Commuting; Migration; Mobility Costs; Uncertainty; Real Options